2022-RA-285-ESGO Real world data of treatment and outcome of patients with early ovarian cancer (FIGO I) in Germany (QS Ovar of the AGO Study Group). (20th October 2022) - Sehouli, Jalid; Bois, Andreas du; Pfisterer, Jacobus; Hilpert, Felix; Kerkmann, Markus; Mahner, Sven; de Gregorio, Nikolaus; Hanker, Lars Ch; Heitz, Florian; Marmé, Frederik; Wölber, Linn Lena; Holtmann, Laura; et al.
Abstract : Introduction/Background: Recent data regarding treatment quality and outcome of patients with early Ovarian Cancer (FIGO I) on a nationwide basis are largely missing for Germany. Methodology: All German hospitals treating patients with ovarian cancer were asked to document all patients with first diagnosis in the third quarter of the years 2004, 2008, 2012 and 2016. Surgery quality was categorized as 'optimal' (OP+: maximum 1 parameter missing), vs 'suboptimal' (OP-). Chemotherapy was defined as optimal according to national guidelines. The overall treatment quality was classified in 3 categories: (1) surgery and chemotherapy optimal (OP+/CT+) versus (2) optimal/suboptimal combined (OP+/CT- or OP-/CT+) versus (3) both suboptimal (OP-/CT-). Results: 19.9% (n=700) of all OC patients were diagnosed FIGO I, of which 47.1% were FIGO IA, 47.9% FIGO IC. Median follow-up period was 51.0 months. Median age was 60 years and 37.1% showed high-grade serous ovarian cancer. The OP+ collective increased from 42.2% to 70.9%. Most common not performed surgical steps were peritoneal biopsies, paraaortic and pelvic lymphadenectomy. Progression-free survival (PFS) and overall survival (OS) were improved with OP+ (84% and 91% at 48-months compared with 71% and 76% with non-optimal surgery: both p<0.001). Optimal chemotherapy standard (CT+) was administered increasingly frequent (71.4% to 80.8%). PFS and OS were prolonged with CT+: 48-months PFS 84% vs. 63% (p<0.001) and 48-months OS 90% vs. 68% (p<0.001). The overall treatment quality cohort 1 increased from 37.9% to 54.1%. 48-months PFS was 86% vs. 76% vs. 62% in group 1 vs. 2 vs. 3, respectively (p<0.001), 48-months OS rates were 93% vs. 81% vs. 68% in group 1 vs. 2 vs. 3, respectively (p<0.001). Conclusion: The QS Ovar shows that the quality of therapy has steadily improved over the years in Germany. Best prognosis could be achieved if surgery and chemotherapy is done according to treatment guidelines.